Pemanfaatan Abu Ampas Tebu Limbah Pabrik Gula Cinta Manis Kabupaten Ogan Ilir Sebagai Additive Beton - Adiguna Adiguna; Agus Wahyudi (Universitas PGRI Palembang, 2020)
ABSTRACTÂ Cane is one of the plantation commodities managed as raw material for making sugar. PT. Cinta Manis as one of the sugar producers has sugarcane production and management activities on a large scale. Production of sugar with raw material in large quantities every day, produces a by-product of sugarcane bagasse waste. Currently sugarcane bagasse waste is only used as compost after going through several stages of processing. The study was conducted in a laboratory by physically changing cane bagasse to ash through burning. Furthermore, the ash from the sugarcane bagasse was added to high quality concrete K-300. The results of the laboratory tests carried out showed that the addition of Cane Bagasse Ash (CBA) by 5% can increase the compressive strength of the concrete 6.43% higher than the normal compressive strength of the concrete. However, the addition of CBA which is greater than 5% to the cement in the concrete actually decreases the quality of the compressive strength of the concrete. This means that the 5% CBA content can be used to increase the compressive strength of concrete.